A Prospective Study on Comparison of Wounds with Effect of Nutrition after Minor Surgery in South India - N.K., Velayudhan; G, Vijay Kumar (Asian Journal of Medical Research, 2018)
Background: A wound is a type of injury which happens relatively quickly in which skin is torn, cut, or punctured or where blunt force trauma causes a contusion (a closed wound). Objective: The objective of this study was to evaluate two groups of patient one group having extra defined supplements at recommended dose and another groups without extra supplements. Subjects and Methods: The present study was conducted on 100 patients out of which 50 were the group having extra supplement with certain amino acids such as arginine, glutathione, etc and also with some vitamins such as vitamin-E and vitamin-C. Patients with the age more than 20 years were included in this study. Patients providing consent were only included in this study. This study was only started after getting all the approval from the college and concern offices. Results: This study shows no case of wound infection and all wound were healed perfectly in patients supplied with extra supplementas compare to control group. In case of control groups (not having any supplement) four patients developed wound discharge. For these 4 patients immediately antibiotics were started. Conclusion: Despite the many years of study and substantial knowledge base of the specific processes and factors involved, wound healing remains enigmatic. There is still much tolearn about the wound-specific nutritional interventions that are available to improve wound healing.